Social presence in digital classrooms: Fostering collaboration and peer interaction in primary education - Arifin Maksum; Arita Marini; Endang M. Kurnianti; Yinghuei Chen; Desy Safitri; Leola Dewiyani; Musril Zahari; Vera Julia; Rezeqi Hardam Saputro; Nindhita Priscillia Muharrani; Asep Marfu (Social Sciences and Humanities Open, 2025)
This study explores the influence of perceived teacher immediacy, platform interactivity, social presence, and peer connectedness on collaborative learning engagement in digital environments. Grounded in social constructivist and media richness theories, the research aims to understand how interpersonal and technological factors shape student participation in online collaborative learning. A quantitative survey methodology was employed, involving 300 primary students from various school. Data were analyzed using partial equation model-structural equation modeling (PLS-SEM) to test the proposed relationships among the variables. The results confirm that all hypothesized paths are statistically significant. Teacher immediacy and platform interactivity positively influence social presence and peer connectedness. Social presence and peer connectedness significantly predicts collaborative learning engagement and mediates the effects of teacher immediacy and platform interactivity on engagement. This study contributes to the growing body of literature on online learning by emphasizing the centrality of social dynamics in digital educational settings. The implications suggest that educators and platform designers should prioritize fostering interpersonal connection and emotional resonance to promote deeper collaborative engagement. Limitations include the cross-sectional nature of the data and reliance on self-reported measures, which may affect the generalizability of the results. Future research may benefit from longitudinal or experimental designs. The study's originality lies in its integrative approach to examining both instructional and technological elements within a cohesive framework, offering a nuanced understanding of what drives student collaboration in digital learning contexts.